Cariad [Love]. Issue 4 (29th September 2021) - Sobande, Francesca
Abstract: I'm still not sure what this poem means to me, let alone what it may mean to other people. However, when revisiting this poem nearly a year since writing it, I felt ready to share a few more words. I wrote this poem in the midst of experiencing loss and grief. I wrote it while spending time with family in Scotland, before returning to where I live in South Wales. Truth be told, I did not write it with the intention of contributing to scholarly work on Black geographies. Instead, the poem was penned in the wee hours of a restless summer night/morning and was part of how I was feeling and writing through grief at the time. In the months since writing this piece, I have had time and space to see things in and through the poem that I did not see before. Reflecting on which words I know in what languages, and how and why I know them. Thinking about the lives of Black people in the predominantly white nations of Scotland and Wales. Considering what it means to live in these devolved nations in Britain, where public conversations concerning Anglocentrism, colonialism, and language often occur in ways that obscure the specific experiences of Black people who do (and don't) speak Scots and Welsh. The place from which this piece was written was a place of grief, restlessness, pain, peace, and remembrance for words, food, time, and love shared with specific people. I'm not sure how to preface a poem, nor am I sure if what I'm prefacing is even a poem at all. Perhaps that is precisely what this is all about. Grasping for certainty, locatedness, and linear narrative and history, while knowing that uncertainty, (dis)location, and divergence is often a part of Black geographies. Abstract : I wrote this poem in the midst of experiencing loss and grief, while spending time with family in Scotland, before returning to where I live in South Wales. Truth be told, I did not write it with the intention of contributing to scholarly work on Black geographies. Instead, the poem was penned in the wee hours of a restless summer night/morning and was part of how I was feeling and writing through grief at the time.